3538 Asthma and Depression in Children: the Role of Family Structure. (27th March 2019) - Shaheen, Magda; Teklehaimanot, Senait
Abstract : OBJECTIVES/SPECIFIC AIMS: Our objective is to examine the relationship between depression, childhood asthma and family structure. METHODS/STUDY POPULATION: We analyzed data from The National Survey of Children's Health 2011-2012 for the variables family structure, parent's smoking, education, poverty, available emotional support, and children's age, gender, race/ethnicity, asthma, physical/mental health, access to care, and insurance. Data were analyzed using multiple logistic regression in STATA 14 (sampling and weight). RESULTS/ANTICIPATED RESULTS: Of the 95, 000 participants, 3.8% had depression, 5.1% had anxiety, 8.5% had emotional, developmental, or behavioral problem, 14.6% had asthma and 19% were single-parent family. Asthmatics had higher chance for depression relative to non-asthmatics (Adjusted Odds Ratio (AOR)=1.5, 95% confidence interval (CI)=1.2-1.8), p=0.001). Those living in a single-family home had higher chance for depression than those living in 2-parents homes (AOR=2.5, 95% CI=1.9-3.2), p=0.001). Other predictors were lack of emotional support, age, poverty <100%, poor health, and smoking parent (p<0.05). DISCUSSION/SIGNIFICANCE OF IMPACT: We concluded that depression was associated with asthma in children from poor single family who lack an emotional support. Management of asthma should include screening and management of psychosocial factors.